2012
DOI: 10.1109/tip.2012.2197628
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expression Recognition in Perceptual Color Space

Abstract: This paper introduces a tensor perceptual color framework (TPCF) for facial expression recognition (FER), which is based on information contained in color facial images. The TPCF enables multi-linear image analysis in different color spaces and demonstrates that color components provide additional information for robust FER. Using this framework, the components (in either RGB, YCbCr, CIELab or CIELuv space) of color images are unfolded to two-dimensional (2- D) tensors based on multi-linear algebra and tensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…However, only gray video clips were used in [14] and [12]. Recent research shows expression recognition gets better performance in the perceptual color spaces [18]. Motivated by these researches, we propose an novel idea to use LBP-TOP on Tensor Independent Color Space (TICS) for micro-expression recognition.…”
Section: Lbp-top On Tics For Micro-expression Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only gray video clips were used in [14] and [12]. Recent research shows expression recognition gets better performance in the perceptual color spaces [18]. Motivated by these researches, we propose an novel idea to use LBP-TOP on Tensor Independent Color Space (TICS) for micro-expression recognition.…”
Section: Lbp-top On Tics For Micro-expression Recognitionmentioning
confidence: 99%
“…To be more robust for the noise, they [17] used elastic net to make TDCS sparse and proposed Sparse Tensor Discriminant Color Space (STDCS). Lajevardi and Wu [18] treated a color facial expression image as a 3rd-order tensor and showed that the perceptual color spaces (CIELab and CIELuv) are better for facial expression recognition than other color spaces.…”
Section: Introductionmentioning
confidence: 99%
“…It concludes that by using grey-scale images we can get facial expression recognition. But we want robust recognition, that's why we have to use color images in proposed method [18].…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Hundred neutral face images of 100 subjects were used for determining the neutral states of faces for extracting the features of [7]. By using a random partition, following the method in [27], 1,200 face images were used for the training set and the remaining 1,200 face images were used for the test set. In the experiment with the proposed method, the training face images with sufficiently high intensities were selected and used for generating intra-class variation images.…”
Section: Comparisons With State-of-the-art Sparse Representation Basementioning
confidence: 99%